Multidisciplinary Observing in the World Ocean’s Oxygen Minimum Zone Regions: From Climate to Fish — The VOICE Initiative - Garçon, Véronique; Karstensen, Johannes; Palacz, Artur; Telszewski, Maciej; Aparco Lara, Tony; Breitburg, Denise; Chavez, Francisco; Coelho, Paulo; Cornejo-D’Ottone, Marcela; Santos, Carmen; Fiedler, Björn; Gallo, Natalya D.; et al. (Frontiers in Marine Science, 2019)
Multidisciplinary ocean observing activities provide critical ocean information to satisfy ever-changing socioeconomic needs and require coordinated implementation. The upper oxycline (transition between high and low oxygen waters) is fundamentally important for the ecosystem structure and can be a useful proxy for multiple observing objectives connected to eastern boundary systems (EBSs) that neighbor oxygen minimum zones (OMZs). The variability of the oxycline and its impact on the ecosystem (VOICE) initiative demonstrates how societal benefits drive the need for integration and optimization of biological, biogeochemical, and physical components of regional ocean observing related to EBS. In liaison with the Global Ocean Oxygen Network, VOICE creates a roadmap toward observation-model syntheses for a comprehensive understanding of selected oxycline-dependent objectives. Local to global effects, such as habitat compression or deoxygenation trends, prompt for comprehensive observing of the oxycline on various space and time scales, and for an increased awareness of its impact on ecosystem services. Building on the Framework for Ocean Observing (FOO), we present a first readiness level assessment for ocean observing of the oxycline in EBS. This was to determine current ocean observing design and future needs in EBS regions (e.g., the California Current System, the Equatorial Eastern Pacific off Ecuador, the Peru–Chile Current system, the Northern Benguela off Namibia, etc.) building on the FOO strategy. We choose regional champions to assess the ocean observing design elements proposed in the FOO, namely, requirement processes, coordination of observational elements, and data management and information products and the related best practices. The readiness level for the FOO elements was derived for each EBS through a similar and very general ad hoc questionnaire. Despite some weaknesses in the questionnaire design and its completion, an assessment was achievable. We found that fisheries and ecosystem management are a societal requirement for all regions, but maturity levels of observational elements and data management and information products differ substantially. Identification of relevant stakeholders, developing strategies for readiness level improvements, and building and sustaining infrastructure capacity to implement these strategies are fundamental milestones for the VOICE initiative over the next 2–5 years and beyond.